2016
DOI: 10.1080/17442508.2016.1155590
|View full text |Cite
|
Sign up to set email alerts
|

Optimal investment to minimize the probability of drawdown

Abstract: We determine the optimal investment strategy in a Black-Scholes financial market to minimize the so-called probability of drawdown, namely, the probability that the value of an investment portfolio reaches some fixed proportion of its maximum value to date. We assume that the portfolio is subject to a payout that is a deterministic function of its value, as might be the case for an endowment fund paying at a specified rate, for example, at a constant rate or at a rate that is proportional to the fund's value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…Furthermore, in combination with Proposition 1, we can see that either drawdown occurs with probability (u, m) = P( < ∞) or the optimal controlled surplus value lies strictly between m and u s , for all time, with probability of 1 − (u, m). The similar conclusion is also derived in the works of Bayraktar and Zhang, 23 Angoshtari et al, 5 and Han et al 6,7…”
Section: Reaching the Safe Levelsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, in combination with Proposition 1, we can see that either drawdown occurs with probability (u, m) = P( < ∞) or the optimal controlled surplus value lies strictly between m and u s , for all time, with probability of 1 − (u, m). The similar conclusion is also derived in the works of Bayraktar and Zhang, 23 Angoshtari et al, 5 and Han et al 6,7…”
Section: Reaching the Safe Levelsupporting
confidence: 87%
“…Note that when = 0, minimizing the probability of drawdown is equal to minimizing the probability of ruin. Angoshtari et al 5 and Han et al 6,7 minimized the probability of drawdown over an infinite-time horizon and showed that the strategy which minimizes the probability of ruin also minimizes the probability of drawdown. Besides, Angoshtari et al 8 and Chen et al 9 computed the optimal investment strategy to minimize the probability of lifetime drawdown for an individual investor.…”
Section: Introductionmentioning
confidence: 99%
“…Under this reinsurance strategy, the value of the surplus process is non-decreasing, so drawdown will never occur. For this reason, we call u s safe level as defined in Angoshtari et al (2016a).…”
Section: Model and Problem Formulationmentioning
confidence: 99%
“…In the second case, the level is not necessarily a fixed one, then the method mentioned above does not apply. Thus, following the analysis of Chen et al (2015) and Angoshtari et al (2016aAngoshtari et al ( , 2016b, we use the technique of stochastic control theory and the corresponding HJB equation to tackle the optimisation problem. In particular, since we constrain the reinsurance proportion in the interval [0,1] for each case, the optimisation problems are discussed in three different situations, which makes the problem more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…We point out that a recent paper by Angoshtari et al (2015b) also studied the minimum drawdown probability problem but over an infinite-time horizon. By utilizing the results of Bäuerle and Bayraktar (2014), the authors found that the minimum infinitetime drawdown probability (MIDP) strategy coincides with the minimum infinite-time ruin probability (MIRP) strategy which consists in maximizing the ratio of the drift of the value process to its volatility squared.…”
Section: Introductionmentioning
confidence: 97%